N‐Acetylserotonin is an oxidation‐responsive activator of Nrf2 ameliorating colitis in rats. Issue 1 (17th October 2022) - Kang, Changyu; Jeong, Seongkeun; Kim, Jaejeong; Ju, Sanghyun; Im, Eunok; Heo, Gwangbeom; Park, Soyeong; Yoo, Jin‐Wook; Lee, Juho; Yoon, In‐Soo; Jung, Yunjin
Abstract: N‐Acetylserotonin (NAS) is an intermediate in the melatonin biosynthetic pathway. We investigated the anti‐inflammatory activity of NAS by focusing on its chemical feature oxidizable to an electrophile. NAS was readily oxidized by reaction with HOCl, an oxidant produced in the inflammatory state. HOCl‐reacted NAS (Oxi‐NAS), but not NAS, activated the anti‐inflammatory nuclear factor erythroid 2‐related factor 2 (Nrf2)‐heme oxygenase (HO)‐1 pathway in cells. Chromatographic and mass analyses demonstrated that Oxi‐NAS was the iminoquinone form of NAS and could react with N‐acetylcysteine possessing a nucleophilic thiol to form a covalent adduct. Oxi‐NAS bound to Kelch‐like ECH‐associated protein 1, resulting in Nrf2 dissociation. Moreover, rectally administered NAS increased the levels of nuclear Nrf2 and HO‐1 proteins in the inflamed colon of rats. Simultaneously, NAS was converted to Oxi‐NAS in the inflamed colon. Rectal NAS mitigated colonic damage and inflammation. The anticolitic effects were significantly compromised by the coadministration of an HO‐1 inhibitor.